Beyond Exchange Relationship: Exploring the Link Between Organizational Justice, Job Involvement, and Citizenship Behavior - Sharma, Abhishek; Sharma, Ankita (The Journal of Behavioral Science, 2021)
Employees’ perceptions of what is and should be fair have been recognized as one of the cognitive factors that influence their attitudes and behaviors at work. Organizations have also realized that employees’ involvement and extra contribution play a big role in today’s ultra-competitive business world. But the empirical exploration of the link between these two realizations is limited. Hence, this study investigated the link between distributive and procedural justice, level of job involvement, and participation in organizational citizenship behavior (OCB). The participants were 87 mid-level managerial personnel working in private sector manufacturing/production organizations in the northern part of India. Perceived fairness (as distributive and procedural justice) was examined as the potential predictor of job involvement and OCB. Multiple regression analysis of data revealed significant and positive contributions of distributive and procedural justice in job involvement (β = 0.24, p = .01 & 0.28, p = .01, respectively) and OCB (β = 0. 43, p = .00 & β = 0.19, p = .05). Demographic factors such as age, experience, and salary were found to have no influence on job involvement, whereas only age predicted significant variance in OCB (β = 0.25, p = .02). Results revealed the far-fetching importance of the perception of justice and proved to contribute to OCB over and above job involvement. The main implication of this research is for organizations with a clear message (empirically supported) that the management, to achieve the desired as well as expected, should reflect on developing a rational mechanism for influencing the perception of employees about the practices and policies related to distributive and procedural justice in the organization.